OPTIMALISASI SISTEM PELAYANAN DAN KINERJA PEMERINTAHAN DESA DI BIDANG PEMBERDAYAAN MASYARAKAT - Titin Sri Wahyuni; Samsul Bahri Pane; Mardiansyah Mardiansyah (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2022)
Optimization is part of maximizing activities so as to realize the desired or desired profit. That with the optimization efforts can be realized activities and or programs effectively and efficiently. This research is based on the service and performance of the Bandar Rejo Village government in the field of community empowerment in Bandar Rejo Village. This study aims to determine the study of village institutions in carrying out their duties and functions to regulate and manage the interests of the community. The research method used is descriptive method with qualitative analysis, namely data collected from interviews with resource persons to describe the service system and performance in the field of community empowerment, through open interviews with the village head's office as many as 4 (three) people. The results show that leadership in community empowerment has been going quite well, but there are still obstacles given that there are associations of citizens who have opinions and thoughts on their lives so that community participation in empowerment activities is not optimal so that there are several work implementation processes that have not been implemented. optimal.